Enfortumab Vedotin Plus Pembrolizumab in Previously Untreated Advanced Urothelial Cancer. Issue 1 (1st January 2023) - Hoimes, Christopher J.; Flaig, Thomas W.; Milowsky, Matthew I.; Friedlander, Terence W.; Bilen, Mehmet Asim; Gupta, Shilpa; Srinivas, Sandy; Merchan, Jaime R.; McKay, Rana R.; Petrylak, Daniel P.; Sasse, Carolyn; Moreno, Blanca Homet; et al.
Abstract : PURPOSE: Cisplatin-based combination chemotherapy remains the standard of care for locally advanced or metastatic urothelial cancer (la/mUC); however, toxicity is substantial, responses are rarely durable, and many patients with la/mUC are ineligible. Each enfortumab vedotin and pembrolizumab have shown a survival benefit versus chemotherapy in UC, are not restricted by cisplatin eligibility, and warrant investigation as a first-line (1L) combination therapy in patients ineligible for cisplatin. METHODS: In this ongoing phase Ib/II, multicenter, open-label study, 1L cisplatin-ineligible patients with la/mUC received enfortumab vedotin 1.25 mg/kg once daily on days 1 and 8 and pembrolizumab 200 mg (day 1) intravenously once daily in 3-week cycles. The primary end point was safety. Key secondary end points included confirmed objective response rate, duration of response (DOR), and overall survival (OS). RESULTS: Forty-five patients received enfortumab vedotin plus pembrolizumab. The most common treatment-related adverse events (TRAEs) were peripheral sensory neuropathy (55.6%), fatigue (51.1%), and alopecia (48.9%). Twenty-nine patients (64.4%) had grade 3 or higher TRAEs; the most common were increased lipase (17.8%), maculopapular rash (11.1%), and fatigue (11.1%). One death (2.2%) was classified as a TRAE. The confirmed objective response rate after a median of nine cycles was 73.3% with a complete response rate of 15.6%. The median DOR and median OS were 25.6 months and 26.1 months, respectively. CONCLUSION: Enfortumab vedotin plus pembrolizumab showed a manageable safety profile. Most patients experienced tumor shrinkage. The median DOR and median OS exceeding 2 years in a cisplatin-ineligible patient population make this a promising combination currently under investigation in a phase III study (ClinicalTrials.gov identifier: NCT04223856 ).